Topics in sports economics - Miceli, Thomas J. (New horizons in the economics of sport, 2025)
This innovative book examines key financial dimensions within the world of sports. Thomas J. Miceli discusses topics ranging from the business nature of sports leagues and the pricing of sports events to college sports and the implementation of sports–related public policies. Viewing sports leagues as competitive economic organizations, Miceli examines the unique aspects of the labour market for professional athletes. Utilising examples from the National Football League, Major League Baseball and the National Collegiate Athletic Association, he expands on athletes’ wages, exploring salary determination, risk sharing and incentives, as well as payment of college-level athletes and players training in the minor leagues. The book discusses the optimal enforcement of rules in sports and the level of punishment required to keep sports fair, evaluating policy issues such as the relationship between sports and gambling and discrimination.